A High‐Capacity, Low‐Cost Layered Sodium Manganese Oxide Material as Cathode for Sodium‐Ion Batteries. Issue 8 (11th June 2014) - Guo, Shaohua; Yu, Haijun; Jian, Zelang; Liu, Pan; Zhu, Yanbei; Guo, Xianwei; Chen, Mingwei; Ishida, Masayoshi; Zhou, Haoshen
Abstract A layered sodium manganese oxide material (NaMn3O5) is introduced as a novel cathode materials for sodium‐ion batteries. Structural characterizations reveal a typical Birnessite structure with lamellar stacking of the synthetic nanosheets. Electrochemical tests reveal a particularly large discharge capacity of 219 mAh g−1 in the voltage rang of 1.5–4.7 V vs. Na/Na+. With an average potential of 2.75 V versus sodium metal, layered NaMn3O5 exhibits a high energy density of 602 Wh kg−1, and also presents good rate capability. Furthermore, the diffusion coefficient of sodium ions in the layered NaMn3O5 electrode is investigated by using the galvanostatic intermittent titration technique. The results greatly contribute to the development of room‐temperature sodium‐ion batteries based on earth‐abundant elements.